Native-valve endocarditis caused by Achromobacter xylosoxidans: a case report and review of literature - Caio Godoy Rodrigues; Jairo Rays; Marcia Yoshie Kanegae (University of São Paulo, 2017)
Achromobacter xylosoxidans is a Gram-negative aerobic bacterium first described by Yabuuchi and Ohyama in 1971. A. xylosoxidans is frequently found in aquatic environments. Abdominal, urinary tract, ocular, pneumonia, meningitis, and osteomyelitis are the most common infections. Infective endocarditis is rare. As far as we know, until now, only 19 cases have been described, including this current report. We report the case of community-acquired native valve endocarditis caused by A. xylosoxidans in an elderly patient without a concomitant diagnosis of a malignancy or any known immunodeficiency. The patient presented with a 2-month history of fever, weight loss, and progressive dyspnea. On physical examination, mitral and aortic murmurs were present, along with Janeway's lesions, and a positive blood culture for A. xylosoxidans. The transesophageal echocardiogram showed vegetation in the aortic valve, which was consistent with the diagnosis of infective endocarditis